Extracellular Vesicles and MicroRNA in Myelodysplastic Syndromes - Mathieu Meunier; David Laurin; Sophie Park (Cells, 2023)
The bone marrow niche plays an increasing role in the pathophysiogenesis of myelodysplastic syndromes. More specifically, mesenchymal stromal cells, which can secrete extracellular vesicles and their miRNA contents, modulate the fate of hematopoietic stem cells leading to leukemogenesis. Extracellular vesicles can mediate their miRNA and protein contents between nearby cells but also in the plasma of the patients, being potent tools for diagnosis and prognostic markers in MDS. They can be targeted by antisense miRNA or by modulators of the secretion of extracellular vesicles and could lead to future therapeutic directions in MDS.